Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Synthesis and catalytic activity of monodisperse gold-mesoporous silica core-shell nanocatalysts - Sekhar, A. C. Sunil; Meera, C. J.; Kottavarithottil Ziyad; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2013)
Core-shell nanostructures, where gold nanoparticles of sub 10 nm size are successfully encapsulated inside porous silica spheres, have been prepared. The detailed characterization of the catalyst shows a high surface area and good mesoporosity. The sinter resistance of the catalyst under repeated cycles of the CO oxidation reaction is observed.